User-policy-based dynamic remote attestation in cloud computing. (2016) - Ba, Haihe; Ren, Jiangchun; Wang, Zhiying; Zhou, Huaizhe; Li, Yiming; Hong, Tie
As one of the most influential technologies, cloud computing brings users more benefits and improves the efficiency of computing in comparison to the traditional model. However, it also introduces a number of unknown risks and challenges, upon which effectiveness and efficiency of those traditional security protection solutions could have very little influence. We introduce DTEM into JVM, which gives robust trust guarantees to Java applications and makes a dynamic attestation about the integrity state of the current applications. DTEM advanced the state of the art in trusted computing and is designed to tackle the dynamic issues by verifying the runtime bytecode integrity of these applications in cloud environments. DTEM not only provides user-defined policy to determine the complexity of integrity checks and the frequency of their executions, but also enhances the availability to pledge the continuous business. What is more, it has less impact on execution performance of cloud applications.